2005
DOI: 10.1051/0004-6361:20053000
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced products from cold coronene clusters

Abstract: Free cold pure coronene clusters have been formed in a gas aggregation source and irradiated with excimer laser pulses. Analysis of the photoproducts thanks to a reflectron time-of-flight mass spectrometer showed that new ionic compounds are formed. These species may include Polycyclic Aromatic Hydrocarbons (PAHs) larger than coronene, PAH-coronene clusters, as well as coronene clusters branched with unsaturated aliphatic chains. The relevance of these results in the context of interstellar medium chemistry, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 59 publications
4
58
0
Order By: Relevance
“…In addition, the spatially resolved observations of the CH band regions in few objects, mainly those that may give rise to the class B and C carriers of the AIBs (Goto et al 2003(Goto et al , 2007, have clearly triggered some new thought. More and more, an interplay between aliphatic and aromatic component is outlined, and the main astrophysical linking ingredient is supposedly the harsh UV irradiation (Goto et al 2003;Bréchignac et al 2005;Goto et al 2007;Sloan et al 2007;Pino et al 2008;Acke et al 2010). …”
Section: Evolutionary Scenarios Based On the 62 And 77 μM Aib Positmentioning
confidence: 99%
“…In addition, the spatially resolved observations of the CH band regions in few objects, mainly those that may give rise to the class B and C carriers of the AIBs (Goto et al 2003(Goto et al , 2007, have clearly triggered some new thought. More and more, an interplay between aliphatic and aromatic component is outlined, and the main astrophysical linking ingredient is supposedly the harsh UV irradiation (Goto et al 2003;Bréchignac et al 2005;Goto et al 2007;Sloan et al 2007;Pino et al 2008;Acke et al 2010). …”
Section: Evolutionary Scenarios Based On the 62 And 77 μM Aib Positmentioning
confidence: 99%
“…To assess the plausibility of this formation process, we should compare it with dissociation mechanisms, which are dominated by photo-evaporation. Laboratory experiments on the photophysics studies of PAH clusters have shown that multiphoton excitation of coronene clusters produced in a gas aggregation source leads to the ejection of van der Waals bonded units (Bréchignac et al 2005;Schmidt et al 2006). The loss of a monomer in the cluster, characterized by a ∼0.76 eV binding energy (Podeszwa 2010), is much more likely to happen upon absorption of a low-energy photon than the breaking of chemical bonds, which require more than 4.8 eV of energy (Pino et al 2007).…”
Section: Implications For Haze Formation In the Stratosphere Of Jupitermentioning
confidence: 99%
“…PAH cations have received close attention with respect to their candidacy as DIB carriers (Alata et al 2010;Bréchignac & Pino 1999;Vanderzwet & Allamandola 1985;Leger & D'hendecourt 1985;Allamandola et al 1985). Salama, Allamandola, and co-workers have systematically examined the spectra of matrix isolated PAH radical cations, generating by in situ VUV photoionization of the isolated PAHs (Salama et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Salama, Allamandola, and co-workers have systematically examined the spectra of matrix isolated PAH radical cations, generating by in situ VUV photoionization of the isolated PAHs (Salama et al 1996). Subsequently, Pino and co-workers used resonant two-photon ionization to prepare Ar tagged clusters of PAH cation radicals, which were then photodissociated to yield action spectra that are expected to closely resemble the absorption spectrum of the bare gas-phase cation (Bréchignac & Pino 1999). In the case of the phenanthrene cation radical, the derived oscillator strengh of the D 0 → D 1 transition (0.15) was some three orders of magnitude larger than inferred from the matrix spectrum.…”
Section: Introductionmentioning
confidence: 99%